Corporate Governance and Institutional Investors: Evidence from Malaysia - Effiezal Aswadi Abdul Wahab; Janice How; Peter Verhoeven (Asian Academy of Management Journal of Accounting and Finance, 2008)
In 2001, Malaysia undertook important corporate governance reforms, which saw the integration of the Malaysian Code on Corporate Governance (MCCG) into Kuala Lumpur Stock Exchange (KLSE) Listing Rules and the establishment of the Minority Shareholder Watchdog Group (MSWG), which aims to enhance institutional investor activism. Following this development, this study investigates the relationship between corporate governance and institutional ownership in Malaysia. Our panel analysis of 434 firms listed on Bursa Malaysia during 1999–2002 finds that institutional ownership is positively and significantly related to corporate governance. However, we find that the relationship becomes less positive after 2001, suggesting that the monitoring effects of institutional ownership and corporate governance arise simultaneously and endogenously.